On the Capacity to Absorb Public Investment : How Much is Too Much? - Gurara, Daniel; Kpodar, Kangni; Presbitero, Andrea; Tessema, Dawit (Washington, D.C. : International Monetary Fund, 2020)
While expanding public investment can help filling infrastructure bottlenecks, scaling up too much and too fast often leads to inefficient outcomes. This paper rationalizes this outcome looking at the association between cost inflation and public investment in a large sample of road construction projects in developing countries. Consistent with the presence of absorptive capacity constraints, our results show a non-linear U-shaped relationship between public investment and project costs. Unit costs increase once public investment is close to 10% of GDP. This threshold is lower (about 7% of GDP) in countries with low investment efficiency and, in general, the effect of investment scaling up on costs is especially strong during investment booms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet